Aspergillus-Derived Galactosaminogalactan Triggers Complement Activation on Human Platelets - Deshmukh, Hemalata; Speth, Cornelia; Sheppard, Donald C.; Neurauter, Magdalena; Würzner, Reinhard; Lass-Flörl, Cornelia; Rambach, Günter (Frontiers in Immunology, 2020)
Invasive fungal infections caused by Aspergillus (A.) and Mucorales species still represent life-threatening diseases in immunocompromised individuals, and deeper knowledge about fungal interactions with elements of innate immunity, such as complement and platelets, appears essential for optimized therapy. Previous studies showed that galactosaminogalactan secreted by A. fumigatus and A. flavus is deposited on platelets, thereby inducing their activation. Since the altered platelet surface is a putative trigger for complement activation, we aimed to study the interplay of platelets with complement in the presence of fungal GAG. Culture supernatants (SN) of A. fumigatus and A. flavus both induced not only GAG deposition but also subsequent deposition of complement C3 fragments on the platelet surface. The SN of a Δuge3 mutant of A. fumigatus, which is unable to synthesize GAG, did not induce complement deposition on platelets, nor did the SN of other Aspergillus species and all tested Mucorales. Detailed analysis revealed that GAG deposition itself triggered the complement cascade rather than the GAG-induced phosphatidylserine exposure. The lectin pathway of complement could be shown to be crucially involved in this process. GAG-induced complement activation on the platelet surface was revealed to trigger processes that might contribute to the pathogenesis of invasive aspergillosis by A. fumigatus or A. flavus. Both pro-inflammatory anaphylatoxins C3a and C5a arose when platelets were incubated with SN of these fungal species; these processes might favor excessive inflammation after fungal infection. Furthermore, platelets were stimulated to shed microparticles, which are also known to harbor pro-inflammatory and pro-coagulant properties. Not only did early processes of the complement cascade proceed on platelets, but also the formation of the terminal complement C5b-9 complex was detected on platelets after incubation with fungal SN. Subsequently, reduced viability of the platelets could be shown, which might contribute to the lowered platelet numbers found in infected patients. In summary, fungal GAG initiates an interplay between complement and platelets that can be supposed to contribute to excessive inflammation, thrombocytopenia, and thrombosis, which are important hallmarks of fatal invasive mycoses.